Contribution of the Algerian Zakat Fund in financing start-ups: A prospective study - Soumia, Loghrab; Houria, Adjila; Hadjer, Lakhdari (International journal of economic perspectives, 2024)
In this article, we are trying to give a forward-looking view of the possibility of integrating the Algerian Zakat Fund into the structures supporting start-ups, with the support of a type of start-up institution that I am entitled to zakat investors and innovators, and we are referring to what is the Algerian Zakat Fund, what are the start-up institutions, and some forms of funding of the Algerian Zakat Fund for Emerging Enterprises (the formula for speculation, participation, leasing, advanced payment sales (bai Salam)). In our view, the Algerian Zakat Fund can finance start-ups, not only at the start-up stage, or only after the start-up, but can be supported and financed at the other stages of the life cycle of Startup institutions. This can be done by raising and developing the proceeds of zakat, respecting the legitimate controls on the investment of zakat funds and respecting the specificities of those institutions.